Ethical Dimensions in Arifin C. Noer’s Drama Scripts: Kapai-Kapai and Pada Suatu Hari - Liza Oktapiani; Vebbi Andra (JPI: Jurnal Pustaka Indonesia, 2023)
This study aimed to examine the ethical dimensions embedded in Arifin C. Noer’s drama scripts Kapai-Kapai and Pada Suatu Hari, with particular emphasis on how moral messages are articulated through character relations and dramaturgical structure. Employing a qualitative content-analysis design, the research analyzed textual documentation of the two scripts using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing, with credibility strengthened through persistent engagement and reference triangulation. The findings reveal three major ethical domains: (1) self-ethics, including honesty, patience, perseverance, and resilience; (2) social and ecological ethics, manifested in helping others, offering counsel, and maintaining harmony with nature; and (3) spiritual ethics, encompassing prayer, gratitude, and faith in God. These dimensions demonstrate how Noer’s dramaturgy frames literature as a moral laboratory in which individual, social, and transcendental responsibilities converge. The study contributes to literary and ethical discourse by highlighting Indonesian drama as a medium of value transmission in contemporary moral education. Nevertheless, as the research is limited to textual analysis without performance-based data, future studies should explore staging practices and audience reception to enrich ethnopoetic and performative perspectives.